2014
DOI: 10.1186/1471-2377-14-136
|View full text |Cite
|
Sign up to set email alerts
|

Anti-leucine rich glioma inactivated 1 protein and anti-N-methyl-D-aspartate receptor encephalitis show distinct patterns of brain glucose metabolism in 18F-fluoro-2-deoxy-d-glucose positron emission tomography

Abstract: BackgroundPathogenic autoantibodies targeting the recently identified leucine rich glioma inactivated 1 protein and the subunit 1 of the N-methyl-D-aspartate receptor induce autoimmune encephalitis. A comparison of brain metabolic patterns in 18F-fluoro-2-deoxy-d-glucose positron emission tomography of anti-leucine rich glioma inactivated 1 protein and anti-N-methyl-D-aspartate receptor encephalitis patients has not been performed yet and shall be helpful in differentiating these two most common forms of autoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
78
1
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(97 citation statements)
references
References 42 publications
15
78
1
3
Order By: Relevance
“…A recent FDG-PET analysis reported hypermetabolism of the sensorimotor cortex in patients with anti-LGI1 encephalitis that, together with contralateral frontal EEG changes and results from polymyographic recordings, are suggestive of a motor cortex origin of FBDS 5. Another FDG-PET study observed hypermetabolism in the precentral gyrus, basal ganglia and cerebellum in patients with LGI1 encephalitis with FBDS 16. Here, precentral hypermetabolism was associated with higher disease severity at follow-up, suggesting that sensorimotor network integrity may serve as a predictor for disease-related disability.…”
Section: Discussionmentioning
confidence: 99%
“…A recent FDG-PET analysis reported hypermetabolism of the sensorimotor cortex in patients with anti-LGI1 encephalitis that, together with contralateral frontal EEG changes and results from polymyographic recordings, are suggestive of a motor cortex origin of FBDS 5. Another FDG-PET study observed hypermetabolism in the precentral gyrus, basal ganglia and cerebellum in patients with LGI1 encephalitis with FBDS 16. Here, precentral hypermetabolism was associated with higher disease severity at follow-up, suggesting that sensorimotor network integrity may serve as a predictor for disease-related disability.…”
Section: Discussionmentioning
confidence: 99%
“…The 6 patients with anti-NMDA encephalitis involved in the study showed regionally limited hypermetabolism in frontotemporal areas contrasting an extensive hypometabolism in parietal lobes, whereas the other group formed of 4 patients with anti-LGI1 encephalitis demonstrated hypermetabolism in cerebellar, basal ganglia, occipital and precentral areas and minor frontomesial hypometabolism (Wegner et al, 2014). In this study, PET imaging abnormalities of the anti-NMDA receptor encephalitis subgroup did not correlate to those detected by MRI in 4/6 patients in the following lesions: hippocampal T2-hyperintensities bilaterally with diffusion elevation, small single unspecific left paraventricular T2-hyperintensity without contrast enhancement or diffusion restriction, multiple very small subcortical T2-hyperintensities with T1-contrast enhancement and faint T2-hyperintensities in both cingular gyri without contrast enhancement.…”
Section: Authorsmentioning
confidence: 95%
“…In this study, PET imaging abnormalities of the anti-NMDA receptor encephalitis subgroup did not correlate to those detected by MRI in 4/6 patients in the following lesions: hippocampal T2-hyperintensities bilaterally with diffusion elevation, small single unspecific left paraventricular T2-hyperintensity without contrast enhancement or diffusion restriction, multiple very small subcortical T2-hyperintensities with T1-contrast enhancement and faint T2-hyperintensities in both cingular gyri without contrast enhancement. In two patients however MRI did not show any lesions (Wegner et al, 2014).…”
Section: Authorsmentioning
confidence: 96%
“…Structural magnetic resonance imaging (MRI) showed extratemporal T2 hyperintensities in the early phase with faciobrachial (dys)tonic seizures (FBDS) and reduced volume of the whole brain one year after FBDS [6][7][8][9][10]. Glucose metabolism is also abnormal in areas outside of the limbic structures [8,[11][12][13]. Although these data point to global structural and metabolic alterations, no study examined metabolic changes several years after LGI1 encephalitis.…”
Section: Introductionmentioning
confidence: 99%